FOMO, Promotions, and Payment Methods Influencing Indonesian E-Commerce Impulse Buying - Rolando, Benediktus (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study examines the influence of Fear of Missing Out (FOMO), sales promotion techniques, and payment methods on impulsive buying behaviour among Indonesian e-commerce consumers. Drawing on the Stimulus-Organism-Response framework and utilizing data from 176 Indonesian online shoppers aged 17-26, this research employs multiple regression analysis to investigate relationships between these variables. Results demonstrate significant positive influences of FOMO (t = 93.482, p < 0.001), sales promotion (t = 95.763, p < 0.001), and payment methods (t = 91.346, p < 0.001) on impulsive buying behaviour. Collectively, these factors explain 68.6% of the variance in impulsive buying behaviour (F = 38.742, p < 0.001), with sales promotion emerging as the strongest predictor. The findings reveal how psychological anxiety about missing opportunities converges with strategic marketing tactics and frictionless payment technologies to create a digital retail environment conducive to spontaneous purchasing decisions. In Indonesia's rapidly evolving e-commerce landscape, characterized by high social media usage and accelerating digital payment adoption (41.3% growth in 2022), these elements represent critical drivers of consumer behaviour. This research advances theoretical understanding of impulsive buying in digital environments while providing practical insights for e-commerce platforms seeking to optimize conversion rates. The study's integrated perspective on psychological, marketing, and technological factors illuminates the complex mechanisms underlying impulsive purchasing decisions in contemporary digital marketplaces, contributing to both theory development and industry practice in an increasingly important domain of consumer behaviour.